Asymmetric conjugate addition reactions with chiral oxadiazinones: Unusual conformational properties of the oxadiazinones. (12th March 2021) - Obe, Fatima Olayemi; Davis, Ryan A.; Spurlock, Jennifer; Grunloh Barnes, Morgan M.; Lindvall, Tyler; Wendorf, Micah S.; Delach, Christina; Ferrence, Gregory M.; Standard, Jean M.; Hitchcock, Shawn R.
Abstract: A series of Ephedra based oxadiazinones have been prepared, acylated, and examined in the asymmetric conjugate addition reaction with Grignard reagents in the presence of copper(I) bromide-dimethyl sulfide complex. The highest diastereoselectivity that was obtained in the conjugate addition reaction was observed with the (1 R, 2 S )-ephedrine based N 4 -methyloxadiazinone (5:1 d.r.) favoring the formation of the ( S )-configuration of the conjugate addition product. Efforts to enhance the level of diastereoselection via increasing the steric volume of the stereo-directing N4 -substituent of the oxadiazinone (N4 - =  p -methoxyphenyl or -isopropyl) led to an observed decrease in the level of diastereoselection. A computational study was conducted to examine the conformations adopted by the N 4 -methyloxadiazinone vs. the N 4 -isopropyl-oxadiazinone that yielded the lower diastereoselectivity. An argument is made for the stereoelectronic properties of the N4 -substituent being the cause of both the moderate diastereoselectivity and the unexpected facial preference for the conjugate addition. Graphical abstract: Image 1 Highlights: Oxadiazinones may serve as templates for the asymmetric aldol but are compromised in conjugate addition reactions. As the steric volume of the stereodirecting N 4 -substituent increases, the diastereoselectivity decreases. Computational studies of the oxadiazinones revealed that the side-chain conformation determines the stereochemical outcome. The N 4 -methyloxadiazinone was demonstrated to have the most stable intermediate in the conjugate addition reaction.